City Image Shaping Elements in Manado’s Megamas - Kaliey, Natalia M.; Dapas, Gisella A.; Gabriel, Rogi D. (CV. Gio Architect, 2024)
The Megamas area encompasses 37 hectares of reclaimed beachfront land, hosting malls, hotels, and recreational spaces vital for bolstering tourism in Manado. Positioned facing Bunaken Island, Megamas stands as a must-visit destination for tourists. Leveraging Kevin Lynch's theory of city image formation, which comprises landmarks, paths, districts, nodes, and edges, this study aims to scrutinize the components shaping the urban identity of Megamas Manado. Employing qualitative methods, the research commenced with on-site observations to gain nuanced insights, followed by questionnaire administration to gauge public perceptions regarding the five elements of city image formation. The findings highlight Megamall as the predominant landmark, with adjacent public spaces serving as nodes, and corridors like Jl. Piere Tendean and thoroughfares such as Jl. E. E. Mangindaan and Jalan K.H. Abdurrahman Wahid acting as pathways. Moreover, shopping centers emerge as prominent districts within the Megamas area.